Asuhan Keperawatan Pada Pasien Dengan Kanker Paru (CA PARU) Di Ruang Rawat Inap Paru Rsup Dr. M. Djamil Padang - Resti Anita Sari; Debby Silvia Dewi; Hilma Yessi; Mike Asmaria (CV. ITTC INDONESIA, 2026)
Lung cancer is a malignancy of the lung tissue or bronchi caused by uncontrolled cell growth and is one of the cancers with the highest mortality rates. According to Globocan 2022 data, there were approximately 2.3 million new cases and 1.8 million deaths from lung cancer. In Indonesia, 408,661 cases were recorded, resulting in 242,099 deaths. This indicates that lung cancer remains a serious health issue requiring attention in prevention and management efforts. An increase in cases has also been observed in West Sumatra, with 1,142 cases at Dr. M. Djamil General Hospital in Padang during the 2021–2025 period. Therefore, this study aims to describe nursing care for lung cancer patients admitted to the pulmonary inpatient ward in 2026. The method used was a case study conducted over 5 days, from January 30 to February 3, 2026, in the Pulmonary Ward of Dr. M. Djamil General Hospital in Padang, involving one patient. The research findings, obtained through interviews, observations, and physical examinations, identified six nursing diagnoses: ineffective airway clearance, ineffective breathing pattern, acute pain, nutritional deficit, sleep disturbance, and risk of infection. The evaluation showed that several issues had been partially resolved, such as airway clearance, ventilatory support, pain, and improved intravenous medication administration, while nutritional deficit and sleep pattern disturbance had been resolved. Following the provision of nursing care, it can be concluded that the patient and family are advised to understand the condition of lung cancer, adhere to treatment and undergo regular follow-ups, adopt a healthy lifestyle, and provide optimal support to improve the patient’s quality of life.